METHODOLOGY FOR COMBINING REAL AND VIRTUAL LABORATORY WORK IN THE EDUCATIONAL PROCESS OF STUDENTS - R.M.Mirsaatov,; S.B.Khudoyberganov,; Sultonov M.U., (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2023)
In higher educational institutions, when receiving higher education, laboratory work becomes a mandatory part of the educational process of engineering and technical specialties, and students in practice study the operation of this or that equipment, the reactions of reagents and chemicals, as well as other equally fascinating processes.